1. The problem statement, all variables and given/known data Ok so I'm having trouble simplifying a part of a boolean equation. It needs to be in the form Yt(.....) 2. Relevant equations note X' means Not X The part to be simplified is.. Y(NX'Z+NX'+NZ') 3. The attempt at a solution Using the rules of simplification, particularly A+A=A, A+A'=1, AxA=1 Ive come down to this but im still unsure if im on the right track.. Y(NX'Z+NX'+NZ') .... so N + N + N = N, X' + X' = X', Z + Z' = 1 Y(NX'(1)) Y(NX') Could someone confirm this, or tell me im completely wrong :uhh: Thankyou!